Local Fishermen’s Preception of Measured Fishing in WPPNRI 714 - Tuhumury, Julian; Tupamahu, Agustinus; Hehanussa, Kedswin G. (Agrikan Jurnal Agribisnis Perikanan, 2025)
The issue of equitable access for local fishermen to marine resources remains a critical concern in the implementation of Measured Fishing (PIT) policies in Indonesia. This study aims to analyze the perceptions of local fishermen regarding PIT, with a specific focus on their access rights in Fisheries Management Area (WPPNRI) 714. The research was conducted from September to November 2023 in several coastal areas in Ambon Island and Banda Neira, Central Maluku. The survey targeted local fishermen operating ring seine (jaring bobo) vessels larger than 5 GT in the villages of Latuhalat, Laha, Waai, and Hitu. Respondents were selected using purposive sampling, and data were analyzed descriptively. Results indicate that most vessel owners support PIT, perceiving its benefits in sustaining fish stocks, optimizing profits, improving data accuracy, and increasing non-tax state revenue. However, many fishermen disagree with the obligation to pay landing fees at designated ports, viewing it as an additional burden. The findings reveal that while the ecological and economic aspects of PIT are generally well-received, issues related to fairness, administrative obligations, and economic impact remain contentious. In conclusion, the successful implementation of PIT requires adaptive and inclusive policies that prioritize sustainability while ensuring the economic viability of local small-scale fishers. These insights are expected to support both regional and national policymakers in formulating fair and context-sensitive fisheries governance.